UPb and SmNd constraints on miocene units in the Ischigualasto-Villa Unión foreland basin, Sierras Pampeanas, Argentina: Sedimentary provenance, landscape evolution coupling flat-slab subduction. (March 2019) - Lemos-Santos, D.V.; Teixeira, W.; Collo, G.; Canelo, H.N.
Abstract: Foreland basin systems are intimately linked to thrust belts and activation and reactivation of structures in association with convergent plate dynamics, capable of controlling regional uplifts, sedimentation, as well as drainage patterns among other processes. The Ischigualasto-Villa Unión basin (IVB) is a Miocene broken foreland, occurring in-between the Famatina-Sañogasta, Valle Fértil and Maz Ranges in the Western Sierras Pampeanas, Argentina, Central Andes. We conducted U–Pb geochronology by SHRIMP in igneous zircons and LA-ICPMS in detrital zircons as well as whole rock Sm–Nd analyses in the Quebrada del Médano and Desencuentro Formations – the uppermost units of the IVB. The new and compiled data provide new insights on the influence of flat-slab on the uplift of the Sierras Pampeanas and Precordillera and consequent shift of the drainage patterns in the basin infill. The SHRIMP age for the youngest zircons from a volcanic tuff of the middle portion of the Desencuentro Formation yielded a mean 206 Pb/ 238 U age of 8.49 ± 0.33 Ma whereas the other grains gave concordant ages from 10 to 1433 Ma. The detrital zircon ages from both Formations indicated that different sourced materials contributed to the basin infill, through time and space. The major age modes in the detrital populations were: 1) 1250-950 Ma, (2) 850-600 Ma, (3) 540-500 Ma, (4) 490-460 Ma, (5) 350-320 Ma, (6) 300-250, (7) 40 Ma and (8) 16-8 Ma. From a statistical point of view, we defined two similar aged groups with distinct major contribution provenance: a first cluster with main Cambrian-Ordovician ages and a second one with main Permian and Mesoproterozoic ages. The bulk picture suggests a critical change in the IVB provenance history since the mid-late Miocene, roughly consistent with the Pampean flat-slab subduction model that controls uplifts of the Western and Eastern Sierras Pampeanas and associated regional drainage shifts in Central Andes, as like geodynamic processes in Western North America. We interpret the statistic change in the distribution of the IVB zircons as product of: (1) the presence of axial rivers flowing parallel to the basement arches in the more distal foreland; (2) a disconnection between the IVB and the Bermejo basin related to the uplift of the IVB western margin; (3) the uprising of the IVB eastern ranges. Our findings are also consistent with the acquired TDM ages (1.2–0.9 Ga) and the coupled εNd(t) constraints (−6 to −5) for samples collected along the stratigraphy of both IVB Formations that indicated recycled Grenville-aged sources were likely overload by sourced rocks with high lithologic erodibility. Highlights: U-Pb geochronology indicated a Miocene age for the Ischigualasto-Villa Unión basin. Major age modes suggested distinct sources in time and space for the basin infill. The Pampean flat-slab subduction controlled the landscape evolution in Central Andes.